Adipokines as Potential Biomarkers in the Neurorehabilitation of Obese Stroke Patients - Ciancarelli, Irene; Morone, Giovanni; Iosa, Marco; Paolucci, Stefano; Pignolo, Loris; Tonin, Paolo; Cerasa, Antonio; Ciancarelli, Maria G. T. (Current Neurovascular Research, 2020)
Background: Limited studies concern the influence of obesity-induced dysregulation of adipokines in functional recovery after stroke neurorehabilitation. Objective: To investigate the relationship between serum leptin, resistin, and adiponectin and functional recovery before and after neurorehabilitation of obese stroke patients. The adipokine potential significance as prognostic markers of rehabilitation outcomes was also verified. Methods: Twenty obese post-acute stroke patients before and after neurorehabilitation and thirteen obese volunteers without-stroke, as controls, were examined. Adipokines were determined by commercially available enzyme-linked immunosorbent assay (ELISA) kits. Functional deficits were assessed before and after neurorehabilitation with the Barthel Index (BI), modified Rankin Scale (mRS), and Functional Independence Measure (FIM). Results: Compared to controls, higher leptin and resistin values and lower adiponectin values were observed in stroke patients before neurorehabilitation and no correlations were found between adipokines and clinical outcome measures. Neurorehabilitation was associated with improved scores of BI, mRS, and FIM. After neurorehabilitation, decreased values of Body Mass Index (BMI) and resistin together increased adiponectin were detected in stroke patients, while leptin decreased but not statistically. Comparing adipokine values assessed before neurorehabilitation with the outcome measures after neurorehabilitation, correlations were observed for leptin with BI-score, mRS-score, and FIM-score. No other adipokine levels nor BMI assessed before neurorehabilitation correlated with the clinical measures after neurorehabilitation. The forward stepwise regression analysis identified leptin as prognostic factor for BI, mRS, and FIM. Conclusion: Our data show the effectiveness of neurorehabilitation in modulating adipokines levels and suggest that leptin could assume the significance of biomarker of functional recovery.
Keywords: neurorehabilitation